A water-soluble polyvinyl alcohol pattern film

By adopting a water-soluble polyvinyl alcohol pattern film, and using a gel reversible polyvinyl alcohol film and a water-based polyvinyl alcohol pattern ink, the pattern decoration without harmful gas release and waste water and waste residue is achieved, and the problems of alcohol solvent use and carrier layer waste in the prior art are solved, and the water resistance and corrosion resistance of the pattern layer are improved.

CN115923368BActive Publication Date: 2025-03-21孙琇芳
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211703300.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-29
Publication Date
2025-03-21
Estimated Expiration
2042-12-29

AI Technical Summary

Technical Problem

The existing decorative layer manufacturing methods for decorative materials pattern have the waste of using alcohol organic solvents and carrier layers in watermarking technology, and the skinning technology leads to environmental pollution and poor water resistance of the product.

Method used

A water-soluble polyvinyl alcohol pattern film is used, which includes a carrier layer, a pattern layer and a pattern protective layer. Through the combination of gel reversible polyvinyl alcohol film, aqueous polyvinyl alcohol pattern ink and transparent printing liquid, no pattern decoration without harmful gas release and wastewater and waste residue are achieved.

Benefits of technology

The pattern decoration process is realized completely with water as the solvent, which reduces the cost of use and environmental pollution, increases the thickness of the pattern layer and anti-corrosion and scratch resistance, and solves the waste problem of the carrier layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure DEST_PATH_IMAGE005
    Figure DEST_PATH_IMAGE005
  • Figure 29492DEST_PATH_IMAGE002
    Figure 29492DEST_PATH_IMAGE002
  • Figure 415474DEST_PATH_IMAGE004
    Figure 415474DEST_PATH_IMAGE004
Patent Text Reader

Abstract

The present invention discloses a water-soluble polyvinyl alcohol pattern film, which is characterized in that: the pattern film comprises a carrier layer, a pattern layer and a pattern protection layer; the carrier layer is made of a gel reversible polyvinyl alcohol film; the pattern layer is made by printing polyvinyl alcohol pattern ink; and the pattern protection layer is made by printing polyvinyl alcohol transparent printing liquid. The water-soluble polyvinyl alcohol pattern film of the present invention uses water as a solvent during use and has no harm to the environment. The method of use is simple, the labor cost is low, and the equipment investment is small. The application range is wide, and it is suitable for artificial marble manufacturing, glass products and military equipment camouflage mapping. It solves the environmental pollution caused by adhesives and pasting patterns in the building decoration industry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of film making and printing, and in particular relates to a water-soluble polyvinyl alcohol pattern film. Background Art

[0002] Most of the existing building decoration materials industry, furniture industry, board making industry, etc. use veneer technology to prepare surface decorative patterns, such as wood veneer, paper veneer, PVC veneer, etc. Another method is hot melt adhesive lamination technology, another method is thermal transfer pattern technology, and some products use high temperature vacuum coating technology.

[0003] Most of the above methods require adhesives or high temperature heating. These laminated products (or panels) are not water-resistant, afraid of moisture and blisters. They will quickly fall off, crack or "peel off" after blisters. The product life is short, and there is environmental pollution and waste of heat energy caused by adhesives. Many products or decorative materials release a large amount of organic pollutants and odors after use, which are harmful to human health.

[0004] Although advanced water printing technology is non-toxic and harmless, the original water printing pattern film still requires alcohol organic solvents to activate and restore the pattern layer, and the carrier layer must be washed away with water after water printing and becomes waste, causing great waste.

[0005] The existing veneer technology also causes air pollution and environmental pollution, which can no longer meet the needs of the development of the building decoration industry, and does not meet the requirements of environmental protection. Summary of the invention

[0006] The invention provides a water-soluble polyvinyl alcohol pattern film to solve the problems existing in the existing method for manufacturing the pattern decoration layer of decorative materials.

[0007] The present invention is achieved through the following technical solutions:

[0008] A water-soluble polyvinyl alcohol patterned film, characterized in that: the patterned film comprises a carrier layer, a patterned layer and a patterned protective layer; the carrier layer is made of a gel reversible polyvinyl alcohol film; the patterned layer is made by printing polyvinyl alcohol patterned ink; the patterned protective layer is made by printing polyvinyl alcohol transparent printing liquid;

[0009] The texture layer comprises the following components by mass fraction:

[0010] Polyvinyl alcohol aqueous solution 40%-50%; triethanolamine acetate 6%-10%; tributyl phosphate 0.1%-0.5%; ethyl ethylene oxide 8%-12%; calcium sulfate 5%-20%; sodium pyrophosphate 1%-3%; boric acid aqueous solution 0.02%-0.3%; chelated titanate coupling agent 0.5%-2%; oxalic acid 0.4%-1%; pigment 4%-15%; ethanol 5%-10%; water (deionized water or purified water) balance;

[0011] The pattern protection layer comprises the following components by mass fraction:

[0012] Polyvinyl alcohol aqueous solution 60%-70%; triethanolamine acetate 6%-10%; tributyl phosphate 0.1%-0.5%; zinc oxide 0.5%-2%; boric acid aqueous solution (concentration 5%) 0.02%-0.3%; 2,4,5,6-tetrachloroisophthalonitrile 0.01%-0.05%; oxalic acid 0.4%-1%; ethyl ethylene oxide 5%-15%; chelated titanate coupling agent 0.5%-3%; diphenyl polysiloxane 0.1%-0.5%; ethanol 5%-10%; water (deionized water or purified water) in appropriate amount; nano silicon dioxide (1000-1500 mesh) 4%-6%.

[0013] Furthermore: the reversible polyvinyl alcohol film has a thickness of 30um-40um, a degree of alcoholysis of polyvinyl alcohol of 99%-99.8%, and a molecular weight of 80,000-120,000.

[0014] Further: the solid content of the polyvinyl alcohol aqueous solution in the texture layer component is 20%-30%, the alcoholysis degree is 87%-89%, the molecular weight is 50,000-80,000, the solid content of the texture layer printing ink is 40%-50%, and the viscosity is 15s-17s / 25°C (coated - 4 cups); the alcoholysis degree of polyvinyl alcohol in the texture protective layer component is 99%-99.8%, and the molecular weight is 50,000-80,000; the solid content of the polyvinyl alcohol aqueous solution is 20%-35%; the solid content of the texture protective layer polyvinyl alcohol (transparent) printing ink is 40%-45%, and the viscosity is 13s-15s / 25°C (coated - 4 cups).

[0015] Furthermore: the printing thickness of the pattern layer is 10um-40um, and the printing thickness of the pattern protection layer is 25um-45um.

[0016] Further: the chelated titanate coupling agent in the pattern layer and the pattern protection layer components is one of di(octylphenol polyoxyethylene ether) phosphate and di(dioctylphosphoryloxy)titanate ethylene glycol.

[0017] The present invention also discloses a method for using the water-soluble polyvinyl alcohol patterned film, which is characterized by comprising the following steps:

[0018] (1) First, spray a layer of water on the surface of the workpiece with a micro-pore spray gun. The thickness of the water surface layer is 20um-45um;

[0019] (2) Stick the water-soluble polyvinyl alcohol pattern film on the surface of the workpiece with the carrier layer facing down and the pattern layer facing up, and gently remove the water bubbles and wrinkles between the pattern film and the workpiece;

[0020] (3) Place the workpiece in parallel in a hot water steam atomization chamber at 95℃-100℃, and first use a micro-pore spray gun to spray water on the surface of the pattern film with a water thickness of 25um-45um; The temperature of the steam atomization chamber is 95℃-100℃. When the water on the pattern film is slowly absorbed by the pattern film and the pattern film changes from a solid state to a swollen gel state, take it out immediately and dry it naturally at room temperature; Place the dried workpiece in a drying room at 120℃-130℃ and dry it for 10min-20min; Take it out after cooling to room temperature.

[0021] The water-soluble polyvinyl alcohol patterned film of the present invention has the following advantages:

[0022] 1. The process of using the printing machine is completely water-based, without any wastewater, waste residue or harmful gas release. Compared with the original water printing technology, the cost of use is greatly reduced. The production and use process are all environmentally friendly and do not cause any harm to the environment.

[0023] 2. Water-soluble polyvinyl alcohol pattern film, during the application process, the carrier layer and the pattern layer are directly applied to increase the thickness of the pattern decoration layer and the anti-corrosion and anti-scratch performance. However, when using the original water printing technology, the polyvinyl alcohol carrier layer must be dissolved and washed away, and it becomes a water-soluble substance for discharge, resulting in a great waste of raw materials. The application process also requires water washing, which increases the water cost and waste of water resources.

[0024] 3. The water-soluble pattern film is easy to use, with low labor costs and small equipment investment.

[0025] 4. It has a wide range of applications, especially in the manufacture of artificial marble, glass products and camouflage patterns for military equipment. It solves the environmental pollution caused by adhesives and pasted patterns in the building decoration industry. DETAILED DESCRIPTION

[0026] The present invention provides a water-soluble polyvinyl alcohol pattern film, which comprises a carrier layer, a pattern layer and a pattern protection layer; the carrier layer is made of a gel reversible polyvinyl alcohol film; the pattern layer is made by printing with a water-based polyvinyl alcohol pattern ink; the pattern protection layer is made by printing with a polyvinyl alcohol transparent printing liquid;

[0027] The texture layer comprises the following components by mass fraction:

[0028] 1. Polyvinyl alcohol aqueous solution 40% - 50%;

[0029] 2. Triethanolamine acetate 6%-10%;

[0030] 3. Tributyl phosphate 0.1% - 0.5%;

[0031] 4. Ethyl ethylene oxide 8% - 12%;

[0032] 5. Calcium sulfate 5%-20%;

[0033] 6. Sodium pyrophosphate 1% - 3%;

[0034] 7. Boric acid aqueous solution (concentration 5%) 0.02% - 0.3%;

[0035] 8. Chelated titanate coupling agent 0.5% - 2%;

[0036] 9. Oxalic acid 0.4% - 1%;

[0037] 10. Pigment 4% - 10%;

[0038] 11. Ethanol 5%-15%;

[0039] 12. An appropriate amount of water (deionized water or purified water);

[0040] The pattern protection layer comprises the following components by mass fraction:

[0041] 1. Polyvinyl alcohol aqueous solution 60% - 70%;

[0042] 2. Triethanolamine acetate 6%-10%;

[0043] 3. Tributyl phosphate 0.1% - 0.5%;

[0044] 4. Zinc oxide 0.5% - 2%;

[0045] 5. Boric acid aqueous solution (concentration 5%) 0.02% - 0.3%;

[0046] 6. 2,4,5,6-Tetrachloroisophthalonitrile 0.01%-0.05%;

[0047] 7. Oxalic acid 0.4% - 1%;

[0048] 8. Ethyl ethylene oxide 5% - 15%;

[0049] 9. Chelated titanate coupling agent 0.5% - 3%;

[0050] 10. Diphenyl polysiloxane 0.1% - 0.5%;

[0051] 11. Ethanol 5% - 10%;

[0052] 12. Water balance;

[0053] 13. Nano-silicon dioxide (1000-1500 mesh) 4%-6%.

[0054] The specific preparation method is as follows.

[0055] 1. Texture layer preparation:

[0056] In the present invention, the carrier layer is made of a gel reversible polyvinyl alcohol film, the film thickness is 30um-40um, preferably 35um, the alcoholysis degree is 99%-99.8%, preferably 99.5%, and the molecular weight is 80,000-120,000, preferably 100,000. In the present invention, the gel reversible polyvinyl alcohol film is purchased from Mudanjiang Shuangxing Chemical Co., Ltd. The model is NTKN-001.

[0057] In the present invention, the pattern layer component includes 40%-50% polyvinyl alcohol aqueous solution, preferably 42%-48%, more preferably 45%-46%; the alcoholysis degree of the polyvinyl alcohol is 87%-89%, preferably 87.5%-88.5%, more preferably 88%, and the molecular weight is 50,000-80,000, preferably 55,000-75,000, more preferably 60,000-70,000. The solid content of the polyvinyl alcohol aqueous solution is 20%-30%, preferably 22%-28%, more preferably 25%-26%. The polyvinyl alcohol aqueous solution can be commercially available or homemade using a polyvinyl alcohol aqueous solution preparation method well known to those skilled in the art, and the preparation process is not particularly limited. In the embodiment of the present invention, Japanese Kuraray products are preferred. The model is NTKN-001.

[0058] In the present invention, the texture layer component includes 6%-10% triethanolamine acetate, preferably 7%-9%, and more preferably 7.5%-8.5%.

[0059] In the present invention, the texture layer component includes 0.1%-0.5% tributyl phosphate, preferably 0.2%-0.4%, more preferably 0.3%-0.35%.

[0060] In the present invention, the texture layer component includes 8%-12% of ethylethylene oxide, preferably 8.5%-11%, and more preferably 9%-10%.

[0061] In the present invention, the texture layer composition includes 5%-20% calcium sulfate, preferably 8%-19%, and more preferably 10%-18%.

[0062] In the present invention, the texture layer component includes 1%-3% sodium pyrophosphate, preferably 1.5%-2.5%, and more preferably 1.8%-2.3%.

[0063] In the present invention, the texture layer component includes 0.02%-0.3% boric acid aqueous solution, preferably 0.05%-0.25%, more preferably 0.1%-0.2% (solution concentration is 5%).

[0064] In the present invention, the texture layer component includes 0.5%-2% of a chelated titanate coupling agent, preferably 0.8%-1.8%, and more preferably 1%-1.6%.

[0065] In the present invention, the texture layer component includes 0.4%-1% oxalic acid, preferably 0.5%-0.8%, and more preferably 0.6%-0.7%.

[0066] In the present invention, the texture layer component includes 4%-15% of pigment, preferably 5%-14%, and more preferably 6%-13%.

[0067] In the present invention, the texture layer component includes 5%-10% ethanol, preferably 6%-9%, and more preferably 7%-8%.

[0068] In the present invention, the texture layer components include an appropriate amount of water, preferably deionized water.

[0069] In the present invention, in the texture layer components, the titanate coupling agent is preferably di(octylphenol polyoxyethylene ether) phosphoric acid. In the embodiment of the present invention, the titanate coupling agent is preferably purchased from Yangzhou Lida Paint Factory.

[0070] In the present invention, the pattern layer printing ink is made by a water-based ink preparation process familiar to those skilled in the art. The solid content of the pattern water-based ink is 40%-50%, preferably 42%-48%, and more preferably 45%-46%. The viscosity is 15s-17s / 25℃, coated-4 cups, preferably 15.5s / 25℃, coated-4 cups.

[0071] In the present invention, the pattern layer is printed by a gravure printing process familiar to those skilled in the art. The printing line speed is preferably 20m / min-30m / min, more preferably 25m / min, and the drying temperature is 45℃-53℃, more preferably 50℃. -3 The distance between the drying air outlet and the film is 100-150 mm, preferably 130 mm. The relative humidity in the printing room is preferably 50%-55%, more preferably 52%.

[0072] In the printing process of the present invention, the viscosity of the water-based ink in the pattern ink fountain needs to be adjusted every 30 minutes or so. The diluent is water + ethanol 90:10, and the amount added each time is 2%-4% of the total amount of the water-based ink. It is added three times and stirred evenly.

[0073] After the pattern layer of the water-soluble polyvinyl alcohol pattern film of the present invention is printed, it needs to be rolled up and dried for a second time at a drying temperature of 50°C. -3 , the line speed is 20m / min, and after drying, a composite film of the carrier layer and the pattern layer is obtained.

[0074] 2. Preparation of pattern protective layer:

[0075] In the present invention, the pattern protection layer component includes 60%-70% polyvinyl alcohol aqueous solution, preferably 62%-68%, more preferably 65%-66%. The solid content of the aqueous solution is 20%-35%.

[0076] The polyvinyl alcohol in the pattern protection layer component has an alcoholysis degree of 99%-99.8%, preferably 99.5%, and a molecular weight of 50,000-80,000, preferably 55,000-75,000, and more preferably 60,000-70,000.

[0077] In the present invention, the pattern protection layer component includes 6%-10% triethanolamine acetate, preferably 7%-9%, and more preferably 8%-8.5%.

[0078] In the present invention, the pattern protection layer composition includes 0.1%-0.5% of tributyl phosphate, preferably 0.2%-0.4%, more preferably 0.3%-0.35%.

[0079] In the present invention, the pattern protection layer composition includes 0.5%-2% zinc oxide, preferably 0.8%-1.8%, more preferably 1.2%-1.5%.

[0080] In the present invention, the pattern protection layer composition includes 0.02%-0.3% boric acid aqueous solution (concentration 5%), preferably 0.08%-0.25%, more preferably 0.15%-0.2%.

[0081] In the present invention, the pattern protection layer composition includes 0.01%-0.05% of 2,4,5,6-tetrachloroisophthalonitrile, preferably 0.02%-0.04%, and more preferably 0.03%-0.035%.

[0082] In the present invention, the pattern protection layer composition includes 0.4%-1% oxalic acid, preferably 0.6%-0.9%, more preferably 0.7%-0.8%.

[0083] In the present invention, the pattern protection layer composition includes 5%-15% of ethylethylene oxide, preferably 8%-13%, and more preferably 10%-11%.

[0084] In the present invention, the pattern protection layer component includes 0.5%-3% of a chelated titanate coupling agent, preferably 1%-2.5%, and more preferably 1.5%-2%.

[0085] In the present invention, the pattern protection layer composition includes 0.1%-0.5% of diphenyl polysiloxane, preferably 0.2%-0.4%, more preferably 0.3%-0.35%.

[0086] In the present invention, the pattern protection layer composition includes 5%-10% ethanol, preferably 6%-9%, more preferably 7%-8%.

[0087] In the present invention, the pattern protection layer composition includes an appropriate amount of water, and the water is deionized water.

[0088] In the present invention, the pattern protection layer composition includes 4%-6% of nano silicon dioxide, preferably 4.5%-5.8%, and more preferably 5%-5.5%.

[0089] In the present invention, the pattern protection layer varnish ink printing liquid is prepared by a water-based varnish ink preparation process well known to those skilled in the art. The pattern protection layer printing liquid has a solid content of 40%-45%, preferably 42%, a viscosity of 13s-15s / 25°C (coating-4 cups), and the pattern protection layer printing thickness is 25um-45um, preferably 30um-42um, and more preferably 35um-40um.

[0090] In the present invention, the pattern protective layer is made by a gravure printing process well known to those skilled in the art. The preferred printing line speed is 20m / min-30m / min, more preferably 25m / min. The drying temperature is 45°C-53°C, preferably 50°C. The distance between the air-drying air outlet and the film is 100mm-150mm, preferably 130mm, and the relative humidity of the printing room is 50%-55%, more preferably 52%.

[0091] In the present invention, the printing thickness of the pattern protection layer printing liquid (ink) is completed by two printings. The present invention uses two plate rollers with the same ink content to print synchronously, and each plate roller prints 1 / 2 of the total thickness. Then the roll is rewound and dried at a drying temperature of 50°C. -3 , the drying line speed is 20 m / min. A water-soluble polyvinyl alcohol pattern film is obtained.

[0092] In the present invention, the printed polyvinyl alcohol pattern film is placed in a dry environment at room temperature for 72 hours before trimming, rolling and packaging. The inner layer of the packaging is waxed kraft paper or tin foil, and the outer layer is a PP plastic packaging bag.

[0093] 3. Application method:

[0094] The water-soluble polyvinyl alcohol pattern film application method of the present invention comprises the following steps:

[0095] (1) First, spray water on the surface (or plane) of the workpiece with a micro-pore spray gun. The thickness of the water surface layer is 20um-45um, and the water surface thickness is uniform. The preferred water surface thickness is 25um-40um. The water temperature is room temperature and is purified water.

[0096] (2) Stick the water-soluble polyvinyl alcohol pattern film on the surface of the workpiece with the carrier layer facing down and the pattern layer facing up. Use an air gun to blow downward gently to remove water bubbles and wrinkles between the pattern film and the workpiece. Before sticking the film, there must be no oil or impurities on the workpiece surface.

[0097] (3) First, use a micro-pore spray gun to spray water on the pattern layer on the surface of the workpiece. The water is purified water with a uniform thickness of 25um-45um. The caliber of the micro-pore spray gun is 1.2mm-1.5mm.

[0098] Place the workpiece in a hot water steam atomization chamber at 95℃-100℃ and atomize it with hot water. When the water on the pattern film is slowly absorbed by the pattern layer and the pattern film changes from solid to gel, take it out and dry it naturally at room temperature.

[0099] The workpiece is placed in a drying room at 120°C-130°C, and dried at a constant temperature for 10min-20min, preferably 15min, and taken out after cooling to room temperature to obtain a pattern decoration layer on the surface of the workpiece (or product).

[0100] The scheme of the present invention is described in detail below with reference to embodiments.

[0101] Examples 1-3

[0102] Material application selection:

[0103] In Example 1, the thickness of the polyvinyl alcohol film of the carrier layer is 30 um.

[0104] In Example 2, the thickness of the polyvinyl alcohol film of the carrier layer is 35 um.

[0105] In Example 3, the thickness of the polyvinyl alcohol film of the carrier layer is 40 um.

[0106] In Example 1, the printing thickness of the pattern layer is 25 um.

[0107] In Example 2, the printing thickness of the pattern layer is 30um-50um, and it is two-color.

[0108] In Example 3, the printing thickness of the pattern layer is 40um-60um, three colors.

[0109] In Example 1, the polyvinyl alcohol in the texture layer has a degree of alcoholysis of 87.5% and a molecular weight of 50,000.

[0110] In Example 2, the polyvinyl alcohol in the textured layer has a degree of alcoholysis of 88% and a molecular weight of 65,000.

[0111] In Example 3, the polyvinyl alcohol in the textured layer has a degree of alcoholysis of 89% and a molecular weight of 75,000.

[0112] In Example 1, the pattern layer chelated titanate coupling agent is di(octylphenol polyoxyethylene ether) phosphate.

[0113] In Example 2 and Example 3, the pattern layer chelated titanate coupling agent is: di(dioctylphosphoxy)ethylene titanate.

[0114] In Examples 1 to 3, the polyvinyl alcoholysis degree of the pattern protection (transparent) layer component is preferably 99%, 99.2%, and 99.5%, respectively, and the molecular weight is 50,000, 60,000, and 70,000, respectively.

[0115] In Example 1 to Example 3, the printing thickness of the pattern protection (transparent) layer is preferably 30um, 35um, and 40um, respectively.

[0116] In Examples 1 to 3, the patterns of the patterned films are preferably marble, agate, and wood. 1. The marble pattern is a single color, which is a light titanium blue. 2. The agate pattern is light yellow and light orange. 3. The wood pattern is light brown, light brown, and light black.

[0117] In Examples 1 to 3, the ratios of the components of the pattern layer and the components of the pattern protection layer are shown in Tables 1 and 2.

[0118] Table 1 Texture layer formula

[0119] Recipe ingredients Scale range Example 1 Example 2 Example 3 1. Polyvinyl alcohol aqueous solution 40%—50% 40% 50% 45% 2. Triethanolamine acetate 6%—10% 6% 8% 10% 3. Tributyl phosphate 0.1%—0.5% 0.1% 0.3% 0.5% 4. Ethyl ethylene oxide 8%—12% 8% 10% 12% 5. Calcium sulfate 5%—20% 20% 5% 10% 6. Sodium pyrophosphate 1%—3% 1% 3% 2% 7. Boric acid aqueous solution (concentration 5%) 0.02%—0.3% 0.05% 0.3% 0.02% 8. Chelated titanate coupling agent 0.5%—2% 0.5% 1% 2% 9. Oxalic acid 0.4%—1% 0.4% 1% 0.6% 10. Pigments 4%—15% 15% 7% 4% 11. Ethanol 5%—10% 7% 5% 10% 12. Water (deionized water or purified water) Moderate Moderate Moderate Moderate

[0120] The pattern layer and printing ink are formulated as follows:

[0121] 1. Monochrome Example 1: The pattern printing ink is formulated according to Table 4, and the pigment is 15% light titanium blue;

[0122] 2. Two-color Example 2: The pattern printing ink is formulated according to Table 4, with the first color pigment being 7% light yellow and the second color pigment being 7% light orange-red;

[0123] 3. Three-color Example 3: the first pigment is 4% light brown, the second color is 4% light brown, and the third color is 40% light black.

[0124] In Example 1 to Example 3, the solid contents of the polyvinyl alcohol aqueous solution were 20%, 25% and 30%, respectively.

[0125] The calcium sulfate is 1000 mesh-1200 mesh, the ethanol is industrial alcohol, and the water is deionized water.

[0126] Table 2 Pattern protective layer formula

[0127] Recipe ingredients Scale range Example 1 Example 2 Example 3 1. Polyvinyl alcohol aqueous solution 60%—70% 60% 70% 65% 2. Triethanolamine acetate 6%—10% 6% 8% 10% 3. Tributyl phosphate 0.1%—0.5% 0.1% 0.3% 0.5% 4. Zinc Oxide 0.5%—2% 0.5% 2% 1% 5. Boric acid aqueous solution (concentration 5%) 0.02%—0.3% 0.02% 0.3% 0.1% 6. 2,4,5,6-Tetrachloroisophthalonitrile 0.01%—0.05 0.01% 0.03% 0.05% 7. Oxalic acid 0.4%—1% 0.7% 1% 0.4% 8. Ethyl ethylene oxide 5%—15% 15% 5% 7% 9. Chelated titanate coupling agent 0.5%—3% 0.5% 3% 1% 10. Diphenyl polysiloxane 0.1%—0.5% 0.1% 0.5% 0.3% 11. Ethanol 5%—10% 10% 5% 7% 12. Water Moderate Moderate Moderate Moderate 13. Nano-silicon dioxide 4%—6% 5% 4% 6%

[0128] In Example 1 to Example 3, the solid contents of the polyvinyl alcohol aqueous solution in the pattern protective layer are respectively 20%, 28%, and 35%.

[0129] The ethanol described is industrial ethanol (95%).

[0130] The nano silicon dioxide is selected to be 1500 mesh.

[0131] The water is deionized water.

[0132] 1. Preparation of Example 1

[0133] 1. Preparation of texture layer

[0134] Using the gravure printing process and gravure water-based ink preparation process well known to those skilled in the art, the raw materials in the components of Example 1 are first made into water-based pattern ink, and the specific steps are as follows:

[0135] 1. First, place 40 parts of polyvinyl alcohol aqueous solution into a vertical grinder, then place 20 parts of calcium sulfate, 15 parts of light titanium blue pigment and 6 parts of triethanolamine acetate into the grinder, the loading amount is 30% of the volume of the grinder, grind at a speed of 200r / min and grind for 4h-10h, and then discharge the material to obtain the first mixed material.

[0136] 2. Add 0.1 parts of tributyl phosphate, 8 parts of ethyl ethylene oxide, 1 part of sodium pyrophosphate, 0.05 parts of boric acid aqueous solution, 0.5 parts of chelated titanate coupling agent, 0.4 parts of oxalic acid and 7 parts of ethanol to the first mixed material in sequence, mix at a speed of 120r / min for 50min, then add appropriate amount of water and mix and adjust the solution to a solid content of 42% and a viscosity of 15s (25°C) (coating -4 cups) to obtain a water-based pattern layer printing ink; before use, filter once or twice, and let it stand for 2h to defoam before use.

[0137] 3. Adjust the printing line speed to 20m / min, the drying temperature to 50℃, the distance between the drying box vent and the printing film to 120mm, and the indoor relative humidity to 50%. Turn on the printing machine to start the pattern layer printing, and the printing thickness is 25um (monochrome). Before the formal printing of the marble pattern, first use PP film (thickness consistent with the carrier film) to print, adjust the line speed and the printing thickness of the ink and the printing effect, and start printing after meeting the requirements.

[0138] 4. After printing, the film is rolled up and dried twice at a temperature of 50°C and a line speed of 30 m / min. After drying, a composite film of a carrier layer and a pattern printing layer is obtained.

[0139] (II) Preparation of pattern protective layer

[0140] (1) First, 5 parts of nano-silicon dioxide are prepared into an aqueous dispersion using a process familiar to those skilled in the art.

[0141] (2) Turn on the mixer, slowly inject 60 parts of polyvinyl alcohol aqueous solution, then slowly inject 5 parts of nano-silica aqueous solution and 0.5 parts of chelated titanate coupling agent at a speed of 120r / min and mix for 30min, then add 6 parts of triethanolamine acetate, 0.1 parts of tributyl phosphate, 0.5 parts of zinc oxide, 0.02 parts of boric acid aqueous solution, 0.01 parts of 2,4,5,6-tetrachloroisophthalonitrile, 0.7 parts of oxalic acid, 15 parts of ethyl oxirane, 0.1 parts of diphenyl polysiloxane, and 10 parts of ethanol, continue to mix at m120r / min for 60min until completely dissolved or mixed evenly. Adjust to a solid content of 40% and a viscosity of 13s / (25℃) to coat-4 cups to obtain a pattern protective layer and printing ink.

[0142] (3) Adjust the gravure printing machine line speed to 20m / min, the drying temperature to 50℃, the distance between the oven vent and the printed film to 120mm, the indoor relative humidity to 50%, start the printing machine and start printing, and the printing thickness is 25um. Before printing, print with PP film first, adjust the printing thickness and printing effect of the ink, and then print on the surface of the pattern layer after meeting the requirements.

[0143] (4) The pattern protection layer (transparent layer) is printed synchronously with two rollers with the same ink content. The printing thickness of each roller is 1 / 2 of the total thickness. After printing, it is rolled back and dried again. The drying line speed is 30m / min and the drying temperature is 50℃. After drying, it is left to stand at room temperature for 72h to obtain a water-soluble polyvinyl alcohol pattern film (marble pattern film).

[0144] (5) After printing, the pattern film is trimmed, rolled and packaged, with waxed kraft paper as the inner layer and PP plastic film as the outer layer, and stored in a ventilated environment at a temperature of 15℃-25℃.

[0145] 2. Preparation of Example 2

[0146] 1. Preparation of texture layer

[0147] (1) Place 50 parts of polyvinyl alcohol aqueous solution into a vertical grinding mill, and then place 5 parts of calcium sulfate, 7 parts of pigment and 8 parts of triethanolamine acetate into the grinding mill in sequence, with the loading amount being 30% of the volume of the grinding mill barrel, and grind at a speed of 250 r / min for 4-10 hours before discharging the material to obtain a first mixed material.

[0148] (2) 0.3 parts of tributyl phosphate, 10 parts of ethyl ethylene oxide, 3 parts of sodium pyrophosphate, 0.3 parts of boric acid aqueous solution, 1 part of chelated titanate coupling agent, 1 part of oxalic acid and 5 parts of ethanol are added to the first mixed material in sequence, mixed with the first mixed material at a speed of 150r / min for 40 minutes, and then an appropriate amount of water is added and mixed evenly, and then adjusted to a solution solid content of 45% and a viscosity of 16s / (25°C) (coated-4 cups) to obtain a water-based pattern layer printing ink. Before use, filter once or twice and let it stand for 1.5 hours before use.

[0149] (3) Adjust the linear speed of the gravure printing machine to 25m / min, the drying temperature to 50℃, the distance between the drying box tuyere and the printing film to 130mm, and the relative humidity in the room to 50%. Turn on the printing machine and print with PP film (thickness of 35um) first, adjust the linear speed and the printing thickness of the ink and the printing effect, and start printing after meeting the requirements. In Example 2, the pattern is a two-color agate pattern, the dark color is light orange, and the light color is light yellow. Two printing inks are made with the same group of formulas in Example 2. When printing, the first plate roller is light-colored, the second plate roller is dark-colored, the printing thickness of the first plate roller is 9um-20um, the printing thickness of the second plate roller is 9um-30um, and the total printing thickness is 50um. .

[0150] (4) After printing is completed, the film is rewound and dried for the second time. The drying temperature is 50°C and the drying line speed is 20 m / min. After drying, a composite film of the carrier layer and the pattern layer is obtained.

[0151] (II) Preparation of pattern protective layer

[0152] (1) 4 parts of nano-silicon dioxide are prepared into an aqueous dispersion using a process known to those skilled in the art.

[0153] (2) Turn on the mixer, slowly inject 70 parts of polyvinyl alcohol aqueous solution, then slowly inject 4 parts of nano-silica aqueous solution and 3 parts of chelated titanate coupling agent, mix at a speed of 150r / min for 25min, then add 8 parts of triethanolamine acetate, 0.3 parts of tributyl phosphate, 2 parts of zinc oxide, 0.3 parts of boric acid aqueous solution (concentration 5%), 0.03 parts of 2,4,5,6-tetrachloroisophthalonitrile, 1 part of oxalic acid, 5 parts of ethyl ethylene oxide, 0.5 parts of diphenyl polysiloxane, 5 parts of ethanol and appropriate amount of water, continue to mix at a speed of 150r / min for 50min, until completely dissolved or mixed evenly. Adjust to a solid content of 42% and a viscosity of 14s / (25℃), apply -4 cups, and obtain a pattern protective layer printing ink.

[0154] (3) Adjust the line speed of the gravure printing machine to 25 m / min, the drying temperature to 50 °C, the distance between the oven vent and the printed film to 130 mm, and the indoor relative humidity to 50%. Turn on the printing machine and first use PP film for trial printing to adjust the printing thickness and printing effect of the ink. After meeting the requirements, start printing the pattern protection layer on the surface of the pattern layer with a printing thickness of 35 um.

[0155] (4) In the present invention, the pattern protection layer (transparent layer) is printed synchronously by two rollers with the same ink content, and the printing thickness of each roller is 1 / 2 of the total thickness. After printing, it is rolled back and dried again, and the drying line speed is 30m / min and the drying temperature is 50°C. After drying, it is left to stand at room temperature for 72h to obtain a water-soluble agate pattern film.

[0156] (5) The printed pattern film is trimmed, rolled up, and packaged. The inner layer is covered with waxed kraft paper, and the outer layer is sealed with PP plastic film and stored in a ventilated environment at a temperature of 15℃-25℃.

[0157] Example 3 Preparation

[0158] 1. Preparation of texture layer:

[0159] (1) Place 45 parts of polyvinyl alcohol aqueous solution into a vertical grinding mill, and then place 10 parts of calcium sulfate, 4 parts of pigment and 10 parts of triethanolamine acetate into the grinding mill in sequence, with the loading amount being 30% of the volume of the grinding mill barrel. Grind at a speed of 300 r / min for 4-10 hours and then discharge the material to obtain a first mixed material.

[0160] (2) 0.5 parts of tributyl phosphate, 12 parts of ethyl ethylene oxide, 2 parts of sodium pyrophosphate, 0.02 parts of boric acid aqueous solution (5% concentration), 2 parts of chelated titanate coupling agent, 0.6 parts of oxalic acid and 10 parts of ethanol are sequentially placed in a mixer and mixed with the first mixed material at a speed of 180r / min for 30 minutes, and then an appropriate amount of water is added and mixed evenly, and the solution solid content is adjusted to 47%, and the viscosity is 17s / (25°C), and 4 cups are applied to obtain a water-based printing ink for the pattern layer. Before use, it is filtered once or twice and then allowed to stand for 1.6 hours before use. In Example 3, the pattern layer is a three-color wood texture, the first color is light brown, and the pigment ratio in the formula ratio is 4%, the second color is light brown, and the pigment ratio in the formula ratio is also 4%, and the third color is light black gray, and the pigment ratio in the formula ratio is 4%. The above three colors use the same formula as Example 3, and except for the pigment component, the other components and ratios remain unchanged.

[0161] When printing, the first roller prints dark gray, the second roller prints light brown, and the third roller prints dark brown.

[0162] (3) Adjust the linear speed of the gravure printing machine to 30 m / min, the drying temperature to 50°C, the distance between the oven vent and the printed film to 150 mm, and the relative humidity in the room to 50%. Turn on the printing machine and first use the PP film to print to adjust the printing thickness and printing effect of the ink. After meeting the requirements, start printing the pattern layer. In Example 3, the pattern layer is a three-color wood texture. The first color is light brown. In the formula ratio, the pigment ratio is 4%. The second color is light brown. In the formula, the pigment ratio is also 4%. The third color is light black gray. In the formula ratio, the pigment ratio is also 4%. The above three colors are made separately using the same group of formulas in Example 3. Except for the pigment, other components and proportions remain unchanged.

[0163] (4) After printing is completed, the film is rewound and dried for the second time. The drying temperature is 50°C and the drying line speed is 30m / min. After drying, a composite film of the carrier layer and the pattern layer is obtained.

[0164] (II) Preparation of pattern protective layer

[0165] 6 parts of nano silicon dioxide were prepared into an aqueous dispersion using a process well known to those skilled in the art.

[0166] Open the mixer, slowly add 65 parts of polyvinyl alcohol aqueous solution, then slowly inject nano-silica aqueous solution and 1 part of chelated titanate coupling agent, mix at a speed of 180r / min for 20min, then add 10 parts of triethanolamine acetate, 0.5 parts of tributyl phosphate, 1 part of zinc oxide, 0.1 parts of boric acid aqueous solution (concentration 5%), 0.05 parts of 2,4,5,6 tetrachloroisophthalonitrile, 0.4 parts of oxalic acid, 7 parts of ethyl ethylene oxide, 0.3 parts of diphenyl polysiloxane and 7 parts of ethanol and appropriate amount of water, continue to mix at a speed of 180r / min for 40min, until completely dissolved and mixed evenly. Adjust to a solid content of 45% and a viscosity of 15s / (25℃) to coat-4 cups to obtain a pattern protective layer printing ink.

[0167] Adjust the printing press line speed to 30m / min, the drying temperature to 50℃, the distance between the oven air outlet and the printed film to 150mm, the indoor relative humidity to 50%, turn on the printing press and first use PP film (thickness of 40um) to print and adjust the line speed, ink printing thickness and printing effect. After meeting the requirements, start printing with a printing thickness of 40um.

[0168] The pattern protection layer (transparent layer) is printed synchronously by two rollers with the same ink content, and the printing thickness of each roller is 1 / 2 of the total thickness. After printing, it is rolled back and dried again, and the drying line speed is 30m / min and the drying temperature is 50°C. After drying, it is left to stand at room temperature for 72h to obtain a water-soluble polyvinyl alcohol pattern film.

[0169] The printed pattern film is trimmed, rolled, and packaged. The inner layer is made of waxed kraft paper, and the outer layer is sealed with PP plastic film and stored in a ventilated environment at a temperature of 15℃-25℃.

[0170] The present invention tests the water-soluble polyvinyl alcohol patterned films of Examples 1 to 3, and the test methods and test results are the same as those of the above technical solution, which will not be repeated here.

[0171] The material sources and technical specifications of Examples 1 to 3 of the present invention are consistent with the above technical solution and will not be described in detail here.

[0172] The application method of the water-soluble polyvinyl alcohol patterned film of Examples 1 to 3 is consistent with the above technical solution and will not be described or exemplified in detail in the examples.

[0173] The water-soluble polyvinyl alcohol pattern film of the present invention uses water as a solvent during production and application, has no harmful gas release, is harmless to the human body, and is harmless to the environment. It can be widely used in the pattern production of metal surfaces, and is particularly suitable for building decoration materials, home furnishing industry, and artificial board manufacturing industry, solving the adhesive pollution problem of veneer technology. The water-soluble polyvinyl alcohol pattern film of the present invention does not need to be washed and discarded with water during the application process of the carrier layer polyvinyl alcohol film, nor does it use any organic solvent, which increases the thickness of the pattern layer and the corrosion resistance of the pattern film to the surface of the workpiece, solves the waste problem of polyvinyl alcohol and the process cost problem of water printing technology, and is an environmentally friendly and economical new pattern decoration material.

[0174] The water solubility test of the embodiment was carried out, and the test method thereof was as follows:

[0175] The water-soluble pattern film is fixed on a plastic frame, placed in a container of water at room temperature, and gradually heated (the heating speed is 10°C every 10 minutes), the water solubility of the film is observed, and the water solubility is recorded. It is found through testing that the water-soluble polyvinyl alcohol pattern film of the present invention is only soluble in hot water above 95°C, insoluble in cold water, and is a thermally reversible pattern film before being dried at a high temperature of 120°C-130°C. Therefore, the water-soluble polyvinyl alcohol pattern film does not absorb water or dissolve in water at room temperature, and can be "filmed" with water at room temperature, and the pattern film will not break or be damaged when exposed to water.

[0176] The present invention tests the water-soluble polyvinyl alcohol pattern film for resistance to vegetable oil, animal oil, salt and alkali, and organic solvents, and observes the oil resistance and salt and alkali resistance. The test method is: fix the water-soluble polyvinyl alcohol pattern film on a plastic frame, and place it in containers of vegetable oil, animal oil, salt water, alkaline water, and ethanol, respectively, at a temperature of 30°C. Observe and record the results as shown in Tables 3 and 4.

[0177] Table 3 Oil resistance test of water-soluble polyvinyl alcohol pattern film

[0178]

[0179] The test results show that:

[0180] The water-soluble polyvinyl alcohol patterned film of the present invention is almost insoluble in plant and animal oils and petroleum hydrocarbons.

[0181] Table 4 Tests on salt resistance, alkali resistance and alcohol resistance of water-soluble polyvinyl alcohol patterned films

[0182]

[0183] The test results show that the water-soluble polyvinyl alcohol patterned film of the present invention has little solubility in alkali salts and alcohols and is almost unaffected.

[0184] The present invention tests the degradation performance of the water-soluble polyvinyl alcohol patterned film, and the test method is as follows: fix the 35um-70um patterned film on a plastic frame, place it in an environment with the same temperature and humidity, and test the degradation rate at different temperatures. The test results are recorded. As shown in Table 5.

[0185] Table 5 Degradation rate test of patterned film

[0186]

[0187] The test results show that the water-soluble polyvinyl alcohol patterned film of the present invention, under the same ambient temperature and ambient humidity, the higher the temperature, the faster the degradation rate. When the temperature rises to 38°C and the relative humidity is 55%, it can be degraded within 60 days.

[0188] The above is a specific technical implementation scheme of the present invention. For ordinary engineering and technical personnel in this field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should be regarded as within the scope of protection of the present invention.

Claims

1. A water-soluble polyvinyl alcohol patterned film, characterized in that: The pattern film comprises a carrier layer, a pattern layer and a pattern protection layer; The carrier layer is made of a gel reversible polyvinyl alcohol film; The pattern layer is made by printing with polyvinyl alcohol pattern ink; The pattern protection layer is made by printing with polyvinyl alcohol transparent printing liquid; The texture layer comprises the following components by mass fraction: Polyvinyl alcohol aqueous solution 40%-50%; Triethanolamine acetate 6%-10%; Tributyl phosphate 0.1%-0.5%; Ethyl ethylene oxide 8%-12%; Calcium sulfate 5%-20%; Sodium pyrophosphate 1%-3%; Boric acid aqueous solution 0.02%-0.3%; Chelated titanate coupling agent 0.5%-2%; Oxalic acid 0.4%-1%; Pigment 4%-15%; Ethanol 5%-10%; Water balance; The pattern protection layer comprises the following components by mass fraction: Polyvinyl alcohol aqueous solution 60%-70%; Triethanolamine acetate 6%-10%; Tributyl phosphate 0.1%-0.5%; Zinc oxide 0.5%-2%; Boric acid aqueous solution 0.02%-0.3%; 2,4,5,6-Tetrachloroisophthalonitrile 0.01%-0.05%; Oxalic acid 0.4%-1%; Ethyl ethylene oxide 5%-15%; Chelated titanate coupling agent 0.5%-3%; Diphenyl polysiloxane 0.1%-0.5%; Ethanol 5%-10%; Water balance; Nano silicon dioxide 4%-6%; The carrier layer has a gel reversible polyvinyl alcohol film, the degree of alcoholysis of the polyvinyl alcohol is 99%-99.8%, and the molecular weight is 80,000-120,000; The polyvinyl alcohol aqueous solution in the texture layer component has a degree of alcoholysis of 87%-89% and a molecular weight of 50,000-80,000; The polyvinyl alcohol in the pattern protection layer component has an alcoholysis degree of 99%-99.8% and a molecular weight of 50,000-80,000.

2. The water-soluble polyvinyl alcohol patterned film according to claim 1, characterized in that: The gel reversible polyvinyl alcohol film has a thickness of 30um-40um, a degree of alcoholysis of polyvinyl alcohol of 99%-99.8%, and a molecular weight of 80,000-120,000.

3. The water-soluble polyvinyl alcohol patterned film according to claim 1, characterized in that: The polyvinyl alcohol aqueous solution in the texture layer component has a solid content of 20%-30%, an alcoholysis degree of 87%-89%, and a molecular weight of 50,000-80,000; the solid content of the texture layer printing ink is 40%-50%, and the coating-4 cup viscosity is 15s-17s / 25°C; the polyvinyl alcohol in the texture protective layer component has an alcoholysis degree of 99%-99.8%, and a molecular weight of 50,000-80,000; the solid content of the polyvinyl alcohol aqueous solution is 20%-35%; The solid content of the polyvinyl alcohol printing ink for the pattern protection layer is 40%-45%, and the coating-4 cup viscosity is 13s-15s / 25°C.

4. The water-soluble polyvinyl alcohol patterned film according to claim 1, characterized in that: The printing thickness of the pattern layer is 10um-40um, and the printing thickness of the pattern protection layer is 25um-45um.

5. The water-soluble polyvinyl alcohol patterned film according to claim 1, characterized in that: The chelated titanate coupling agent in the pattern layer and the pattern protection layer components is one of di(octylphenol polyoxyethylene ether) phosphate and di(dioctylphosphoryloxy)titanate ethylene glycol.

6. The method for using the water-soluble polyvinyl alcohol patterned film according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) First, spray a layer of water on the surface of the workpiece with a micro-pore spray gun. The thickness of the water surface layer is 20um-45um; (2) Stick the water-soluble polyvinyl alcohol pattern film on the surface of the workpiece with the carrier layer facing down and the pattern layer facing up, and gently remove the water bubbles and wrinkles between the pattern film and the workpiece; (3) Place the workpiece in parallel in a 95℃-100℃ hot water steam atomization chamber, and first use a micro-pore spray gun to spray water on the surface of the pattern film, with a water surface thickness of 25um-45um; The temperature of the steam atomization chamber is 95℃-100℃. When the water on the patterned film is slowly absorbed by the patterned film and the patterned film changes from a solid state to a swollen gel state, it is immediately taken out and dried naturally at room temperature. Place the dried workpiece in a drying room at 120℃-130℃ and dry it for 10min-20min; take it out after cooling to room temperature.

Citation Information

Patent Citations

  • Gel reversible polyvinyl alcohol film

    CN105385257A

  • Poly(vinyl alcohol) waterborne intaglio printing UV ink and a preparation method thereof

    CN108753034A

  • Manufacturing method of functional thin film

    TW201231266A